ANALISIS PENGGUNAAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PPKn - Wulandari, Fitri; Utomo, Bambang Budi; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the use of Make A Match learning model to improve the students’ learning outcomes in Civic Education subject at class X MIA of SMA Taman Mulia. The conducted study comprises the teaching and learning process using the applied learning model and the analysis of the learning results. This is a descriptive study in the form of a survey in which the discussion is presented qualitatively. The subject of the research was the tenth-grade students of Science class at SMA Taman Mulia. The data collection techniques applied were direct communication and observation. The data analysis comprises 1. Data evaluation from interviews and observation such as field notes, personal documents, official documents, pictures, photos, 2. Data reduction, 3. Data validation, and 4. Data interpretation. The results of the analysis show that the applied cooperative learning model improves students’ learning outcomes in the Civic Education subject on tenth-grade students of Science class at SMA Taman Mulia.Keywords: Cooperative Learning Model, Make a Match, Learning Outcomes, Civic Education